Trends and burden of gout among adolescents aged 10–24 years: insights from the global burden of disease study 2021 - Pang, Yueshan; Yuan, Yiran; Zhou, Wei; Liu, Shan; Du, Yanbin (Frontiers in Public Health, 2025)
BackgroundGout increasingly affects adolescents. However, comprehensive data on adolescent gout are scarce. This study aimed to analyse the incidence, prevalence, years lived with disability (YLDs), and risk factors for gout in adolescents aged 10–24 years via the Global Burden of Disease (GBD) database from 1990 to 2021.MethodsThis study employed cross-sectional data from the GBD 2021 study in adolescents aged 10–24 years. The incidence, prevalence, YLD, and risk factor rates or numbers for gout were extracted, and trends across different sociodemographic index (SDI) levels and exponential annualized percentage change (EAPC) rates were analysed via linear regression analysis. Bayesian age-period-cohot (BAPC) model with an integrated nested Laplace approximation to predict the age-standardized incidence rate of gout among adolescents over the next 15 years in Global, China, Taiwan (Province of China), Qatar, and Maldives.ResultsThe global incidence number of gout in adolescents increased by 23.47% (95% CI 21.66 to 25.92) from 1990 to 2021; by 2021, the incidence number of gout was 110664.59 (95% UI 62543.83 to 163447.37). High BMI was the leading risk factor for YLD. The higher the SDI is, the greater the incidence of gout and the greater the disease burden in adolescents. Taiwan (Province of China) had the highest rates in 2021, and an increasing trend is predicted by 2035.ConclusionAdolescent gout is an escalating global health issue, particularly in regions with increasing age-standardized incidence rates. Urgent dietary and weight interventions are recommended to reduce the disease burden in adolescents.